Effect of thermal changes of mouth environment by hot and cold drinks on the temperature of implants - Mahmod Kazemi; Saeed Nokar; Ahmad Rohanian; Adel Pazhohan (Tehran University of Medical Sciences, 2013)
Background and Aims: Thermal changes in the oral cavity can be transferred to the implants placed in bone and affect the prognosis of the treatments. Furthermore, some investigators proposed improvement of habitual consumption of hot or cold beverages. The aim of the present study was to measure the effect of temperature changes in the oral cavity following consumption of hot and cold drinks on the temperature of implant.   Materials and Methods: In this clinical trial, 3 eligible patients were selected. Two months after implant insertion, temperature of the implants was measured following the drinking of hot and cold beverages using a sensor connected to a thermometer. The thermal changes of the implants through the different time intervals were analyzed using Friedman non-parametric test.   Results: The implant temperatures were significantly increased in the time following drinking of the hot beverages (P=0.009). Furthermore, the implant temperature were statistically decreased in the time after drinking cold beverage (P=0.004). When drinking hot beverages, the maximum and minimum temperatures were 41.57 0 C and 36.77 0 C, respectively. The maximum and minimum temperatures of the implants were also 34.13 0 C and 26.83 0 C , respectively, when drinking cold beverages.   Conclusion: It seems that the temperatures noted in the implants in the current study cannot weaken the prognosis of implant restorations; however, habitual consumption of hot and cold beverages can lead to debilitating implant prognosis and therefore, should be given the necessary warnings to patients.